LEARNINGS MODEL INFLUENCE TAKE AND GIVE TO USUFRUCT SUBJECT STUDENT STUDYING CONVERTS ENERGY ON BASICS PRINCIPLE BASE INTEREST OF MOTOR BAKAR CLASS X TEKNIK KENDARAAN RINGAN (TKR) AT SMK NEGERI 1 PALANGKARAYA SCHOOL YEAR 2015/2016 - Wahyu Julianur Permad; Jhonni Rentas Duling (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
This research aims to know the influence learning model of students studying on basic principle based on interest to motor burning subject at class x TKR SMKN 1 Palangka Raya. To assess student upon learning by utilizing a conventional method that gets lowest discourse character at under average value which is 68,45. Meanwhile minimal thoroughness criterion 70, therefore it needs to be done by improvement in studentâ€™s learning activity. One of effort which can be done in achieving a success namely, teacher can choose and applies a relevant learning model with teaching material for students. By using the learning model â€œTake And Giveâ€ can be active in notice learning in which student can mutually interact the information to classmate. The sample is done by using Random Sampling. First sample involved 33 students in TKR which is as class of experiment utilizing in learning model Take And Give. The next sample took 31 students be in TPM as control class by using a conventional learning of models that used to the model learning. This adopted the research experiments. In this study, the intrument is using the double helix to collect a result data. Then it was analyzed by the data tests normality, homogeneity quiz, and quiz t, test normality for Post is Test Experiment class which is x2 computing < 2x tablel, which is 7,959 <11, 070. Normality quiz Post is Test class controls computing < tablel, which is 9, at 240< 9,488, the test homogeneity is gotten Fhitung= (1.11) < Ftable (1.82), and homogeneous has been stated. Finally it can conclude that t computing = 3,76 > ttable = 1,999 thus Ho is refused and Ha is accepted. Ha is available result of influence studies by using the type learning model Take And Give on basic principle motor burning on X TKR SMKN 1 Palangka Raya School Year 2015 / 2016.